Bioactive Compounds and Antioxidant Activity of Lettuce Grown in Different Mixtures of Monogastric-Based Manure With Lunar and Martian Soils - Duri, Luigi G.; Pannico, Antonio; Petropoulos, Spyridon A.; Caporale, Antonio G.; Adamo, Paola; Graziani, Giulia; Ritieni, Alberto; De Pascale, Stefania; Rouphael, Youssef (Frontiers in Nutrition, 2022)
The supplementation of bioactive compounds in astronaut’s diets is undeniable, especially in the extreme and inhospitable habitat of future space settlements. This study aims to enhance the Martian and Lunar regolith fertility (testing two commercial simulants) through the provision of organic matter (manure) as established by in situ resource utilization (ISRU) approach. In this perspective, we obtained 8 different substrates after mixing Mojave Mars Simulant (MMS-1) or Lunar Highlands Simulant (LHS-1), with four different rates of manure (0, 10, 30, and 50%, w/w) from monogastric animals. Then, we assessed how these substrates can modulate fresh yield, organic acid, carotenoid content, antioxidant activity, and phenolic profile of lettuce plants (Lactuca sativa L.). Regarding fresh biomass production, MMS-1-amended substrates recorded higher yields than LHS-1-ones; plants grown on a 70:30 MMS-1/manure mixture produced the highest foliar biomass. Moreover, we found an increase in lutein and β-carotene content by + 181 and + 263%, respectively, when applying the highest percentage of manure (50%) compared with pure simulants or less-amended mixtures. The 50:50 MMS-1/manure treatment also contained the highest amounts of individual and total organic acids, especially malate content. The highest antioxidant activity for the ABTS assay was recorded when no manure was added. The highest content of total hydroxycinnamic acids was observed when no manure was added, whereas ferulic acid content (most abundant compound) was the highest in 70:30 simulant/manure treatment, as well as in pure LHS-1 simulant. The flavonoid content was the highest in pure-simulant treatment (for most of the compounds), resulting in the highest total flavonoid and total phenol content. Our findings indicate that the addition of manure at specific rates (30%) may increase the biomass production of lettuce plants cultivated in MMS-1 simulant, while the phytochemical composition is variably affected by manure addition, depending on the stimulant. Therefore, the agronomic practice of manure amendment showed promising results; however, it must be tested with other species or in combination with other factors, such as fertilization rates and biostimulants application, to verify its applicability in space colonies for food production purposes.